posted by on .

I posted this below and received help but im still lost and worked out the problem but am getting the wring answer:

--------------------
Given the equilibrium constant values:

1.N2(g)+ 1/2O2(g)<---> N2O(g)
KC=2.7*10^{-18}

2.N2O4(g)<----> 2NO2(g)
KC= 4.6*10^{-3}

3. 1/2N2(g)+ O2(g)<----> NO2(g)
KC=4.1*10^{-9}

-----------------------------
2N2O(g)+ 3O2 (g) <----> 2N2O4(g)

I need help i dunt know what to do next Part:

1.2N2(g)+ O2(g)<---> 2N2O(g) (*2)
KC=5.4*10^{-18}

2.2NO2<----> N2O4(g)
KC= 1/4.6*10^{-3}

I know i flip the second equation so Kc is flipped over 1...and i multiplied the 1st equation by 2:

Now i don't know what to do i don't know how they got to the final equation.

Responses

Reverse 1.
Multiply 3 by 2.
Reverse 2.
Add the equations and you get 1/2 of the equation you want (if I didn't goof), then double that (and square the resulting K).

-----------------------------------

Okay so this is what i did:

1.FLIP= N2O <--> N2 + 1/2O2
Kc= 1/2.7*10^{-18}= 3.7*10^17

2. FLIP= 2NO2 <---> 2NO2O4
Kc= 1/4.6*10^{-3}= 217.39

3. MULTIPLY BY 2
N2 + 2O2 <---> 2NO2
Kc= 4.1*10^{-9} * 2= 8*10^-9

---------------------------------

THE FINAL EQUATION SHOULD BE :

2N2O(g)+ 3O2 (g) <----> 2N2O4(g)

AND I'M NOT GETTING IT RIGHT AND I DON'T UNDERSTAND WHAT GETS CANCELED OUT I'M CONFUSED AND THE FINAL Kc I KEEP GETTING IS WRONG...

Here is my take on the question without any guarantees:
1. Reverse and multiply by 2
N2(g)+ 1/2O2(g)<---> N2O(g) Kc=2.7*10^-18
2N2O –> 2N2 + O2 K1 = [1 / 2.7*10^-18]^2

2. Reverse and multiply by 2
N2O4(g)<----> 2NO2(g) Kc= 4.6*10^-3
4NO2 –> 2N2O4 K2 = [1 / 4.6*10^-3]^2

3. Multiply by 4
1/2N2(g)+ O2(g)<----> NO2(g) Kc=4.1*10^-9
2N2+ 4O2<----> 4NO2 K3 = [4.1*10^-9 ]^4

Adding left sides and right sides, and doing cancellations, we get:
2N2O(g)+ 3O2 (g) <----> 2N2O4(g) K = (K1)(K2)(K3)

When I worked the problem for you a couple days ago, I arrived at an equation with 1/2 the coefficients but I squared the final K which would have been correct. However, I DID NOT square the reverse of 2 after I multiplied the equation by 2. GK is correct and I goofed. The rest of my answer procedure correct.